Implikasi Hukum Pernikahan Online (Virtual Marriage) Terhadap Keabsahan Dan Akibat Hukumnya Dalam Perspektif Fiqh Dan Regulasi Di Indonesia - Miftakur Rohman; Fashihuddin Arafat (MASADIR: Jurnal Hukum Islam, 2025)
The development of information and communication technology has given rise to the phenomenon of online marriage, a practice that challenges traditional norms in Islamic family law and Indonesian national regulations. This study aims to analyze the validity of online marriage from the perspective of Islamic Fiqh (Islamic jurisprudence) and Indonesian laws and regulations, and to identify the legal implications arising, particularly regarding the rights and obligations of husband and wife, the status of children, joint property, and divorce procedures. Using normative legal research methods, this study examines various Islamic jurisprudence schools of thought, contemporary fatwas, Law Number 1 of 1974 concerning Marriage, the Compilation of Islamic Law, and relevant Ministerial Regulations of the Minister of Religious Affairs, as well as court decisions. The findings indicate differences of opinion among Islamic jurists regarding the concepts of ittihad al-majlis (unity of assembly) and sighat (the wording of the ijab qabul) in a virtual context. Although Indonesian regulations have accommodated online marriage registration and the witnessing of the ijab qabul through a virtual representative, there are no explicit provisions governing the validity of in-person online marriage contracts. This gap creates legal uncertainty, particularly for unregistered marriages, which results in the vulnerability of wives' and children's rights. This study concludes the importance of harmonizing religious and positive law to provide comprehensive legal certainty and protection for couples who marry online.